Peran Program Food Rescue Organisasi Garda Pangan dalam Meningkatkan Food Waste Awareness - Dyva Claretta; Talitha Pandya; Thania Putri Moeksim; Juliana Nur Rachmah (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Indonesia is one of the largest food waste producing countries and has a high hunger value index. Public awareness and participation in reducing food disposal activities are needed to reduce the hunger value index in Indonesia. The focus of this research is the role of Garda Pangan in the eyes of its social media followers as a potentially wasted food collection organization to be distributed to people in need. The purpose of this research is to determine the role of the Food Rescue program carried out by Garda Pangan in increasing food waste awareness. The research method used is a descriptive method with a qualitative approach. Data collection in this study was obtained from interviews and literature review activities. The results showed that Garda Pangan organization helped increase awareness of its social media followers about food waste and took part in distributing potentially wasted food to people in need